2019
DOI: 10.1111/1471-3802.12473
|View full text |Cite
|
Sign up to set email alerts
|

Opening Oz's curtain: who’s really running the annual IEP meeting to discuss secondary transition issues?

Abstract: We conducted a qualitative analysis of written transcripts from nine teacher‐led middle and high school IEP meetings for students with learning disabilities to determine common themes regarding student roles during these meetings and the meeting process itself. We found two overall meta‐themes (e.g., instant vision and out of focus), seven themes (e.g., whose meeting is this, clear as mud, ignoring stated needs) and five subthemes (e.g., better left unsaid, form‐driven meetings, one size fits all). Even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The study conducted by Cavendish and Connor (2018) features data from 17 teachers and focuses on factors influencing parent and student engagement in IEP and transition planning (i.e., older students). Doronkin et al, (2020) focused specifically on IEP involvement for middle and high school students with learning disabilities. On the other hand, the study conducted by Danneker and Bottge (2009) only focused on elementary school students.…”
Section: Barriers To Student-led Iep Meetingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Cavendish and Connor (2018) features data from 17 teachers and focuses on factors influencing parent and student engagement in IEP and transition planning (i.e., older students). Doronkin et al, (2020) focused specifically on IEP involvement for middle and high school students with learning disabilities. On the other hand, the study conducted by Danneker and Bottge (2009) only focused on elementary school students.…”
Section: Barriers To Student-led Iep Meetingsmentioning
confidence: 99%
“…Landmark and Zhang (2019) observed high school IEP meetings, finding that students spoke during 13% of time intervals.These low levels of student participation may be a result of traditional teacher-led IEP meetings, where school staff act as gatekeepers in a "chairman of the board" role. When IEP meetings are teacher-led, students are often given limited opportunities to contribute (Doronkin et al, 2020). From interviews with students, Munsell and Schwartz (2022) found that students often perceive IEP meetings as disciplinary, exclusionary, and anxiety-provoking.…”
mentioning
confidence: 99%
“…Previous research on parents' and pupils' participation in the IEP process, some of which involves pupils with intellectual disabilities, has focused on their participation levels [23] and regional discrepancies [24]; parents' experiences [25,26], input [27], and interactions during the IEP meeting [28]; pupils' roles [29]; and student-led IEP meetings [30]. However, this previous research has revealed a power imbalance between schools and families, which can lead to families having a diminished role in the process.…”
Section: Challenges and Collaboration In The Iep Goal-setting Processmentioning
confidence: 99%
“…Families have often been left outside the decision-making process and decisions concerning goals might have been made before the meeting; see [17,27,28,[31][32][33]. In addition, pupils' participation has been reported as being notably sparse, especially among pupils with lower functional cognitive and social skills; see [23,29,[34][35][36][37].…”
Section: Challenges and Collaboration In The Iep Goal-setting Processmentioning
confidence: 99%
“…However, researchers must also further explore the dynamics of the transition planning process to identify other potential barriers to student involvement. For example, Doronkin et al (2020) conducted a phenomenological study of Individualized Education Program (IEP) meetings for nine high school students with LD, finding that meetings tended to be teacher-led, rushed, and impersonal. This research confirmed and expanded prior quantitative research on students’ feelings of discomfort during IEP meetings (Martin et al, 2004).…”
mentioning
confidence: 99%